High-quality permanent draft genome sequence of the Bradyrhizobium elkanii type strain USDA 76T, isolated from Glycine max (L.) Merr - Reeve, W.; van Berkum, P.; Ardley, J.; Tian, R.; Gollagher, M.; Marinova, Dora; Elia, P.; Reddy, T.; Pillay, M.; Varghese, N.; Seshadri, R.; Ivanova, N.; et al. (Michigan State University, 2017)
Â© 2017 The Author(s). Bradyrhizobium elkanii USDA 76 T (INSCD = ARAG00000000), the type strain for Bradyrhizobium elkanii, is an aerobic, motile, Gram-negative, non-spore-forming rod that was isolated from an effective nitrogen-fixing root nodule of Glycine max (L. Merr) grown in the USA. Because of its significance as a microsymbiont of this economically important legume, B. elkanii USDA 76 T was selected as part of the DOE Joint Genome Institute 2010 Genomic Encyclopedia for Bacteria and Archaea-Root Nodule Bacteria sequencing project. Here the symbiotic abilities of B. elkanii USDA 76 T are described, together with its genome sequence information and annotation. The 9,484,767 bp high-quality draft genome is arranged in 2 scaffolds of 25 contigs, containing 9060 protein-coding genes and 91 RNA-only encoding genes. The B. elkanii USDA 76 T genome contains a low GC content region with symbiotic nod and fix genes, indicating the presence of a symbiotic island integration. A comparison of five B. elkanii genomes that formed a clique revealed that 356 of the 9060 protein coding genes of USDA 76 T were unique, including 22 genes of an intact resident prophage. A conserved set of 7556 genes were also identified for this species, including genes encoding a general secretion pathway as well as type II, III, IV and VI secretion system proteins. The type III secretion system has previously been characterized as a host determinant for Rj and/or rj soybean cultivars. Here we show that the USDA 76 T genome contains genes encoding all the type III secretion system components, including a translocon complex protein NopX required for the introduction of effector proteins into host cells. While many bradyrhizobial strains are unable to nodulate the soybean cultivar Clark (rj1), USDA 76 T was able to elicit nodules on Clark (rj1), although in reduced numbers, when plants were grown in Leonard jars containing sand or vermiculite. In these conditions, we postulate that the presence of NopX allows USDA 76 T to introduce various effector molecules into this host to enable nodulation.